Perencanaan Sistem Pengangkutan Sampah dengan Metode Dinamis di UPTD Tumpang - Mohammad Mirwan; Aura Maulidah (Prosiding ESEC, 2022)
The generation of waste will increase every year. Therefore, a good waste management system is needed to minimize the negative impact of the waste itself. One of the waste processing is the transportation of waste from TPS to TPA. The generation of waste itself is influenced by the population. The number of residents served by UPTD Tumpang is 542120 people in 2021. The sub-districts served by UPTD Tumpang are Pakis District, Jabung District, Tumpang District, Poncokusumo District, Wajak District and Tajinan District. Garbage collected at TPS as much as 258.6 m/day will be transported to TPA Paras Poncokusumo. The generation of waste that increases every year requires efficient route management and provision of fleets. This study aims to discuss the projected waste generation that will affect fleet requirements and traffic in the next 10 years. Using a dynamic model by utilizing the Stella software, it is possible to find out the needs of the fleet and the flow of waste transportation in the coming year based on waste generation. The results of this research in 2022 in the form of fleet needs as many as 11 units and 36 cycles per day. In the existing condition, there are 10 fleets and 38 rides, so from these differences it can be seen the reduction in distance, fuel costs, and vehicle emissions.